Over a third of palliative medicine physicians meet burnout criteria: Results from a survey study during the COVID-19 pandemic. (March 2023) - Boland, Jason W; Kabir, Monisha; Spilg, Edward G; Webber, Colleen; Bush, Shirley H; Murtagh, Fliss; Lawlor, Peter G
Background: Palliative medicine physicians may be at higher risk of burnout due to increased stressors and compromised resilience during the COVID-19 pandemic. Burnout prevalence and factors influencing this among UK and Irish palliative medicine physicians is unknown. Aim: To determine the prevalence of burnout and the degree of resilience among UK and Irish palliative medicine physicians during the COVID-19 pandemic, and associated factors. Design: Online survey using validated assessment scales assessed burnout and resilience: The Maslach Burnout Inventory Human Services Survey for Medical Personnel [MBI-HSS (MP)] and the Connor-Davidson Resilience Scale (CD-RISC). Additional tools assessed depressive symptoms, alcohol use, and quality of life. Setting/participants: Association of Palliative Medicine of UK and Ireland members actively practising in hospital, hospice or community settings. Results: There were 544 respondents from the 815 eligible participants (66.8%), 462 provided complete MBI-HSS (MP) data and were analysed. Of those 181/462 (39.2%) met burnout criteria, based on high emotional exhaustion or depersonalisation subscales of the MBI-HSS (MP). A reduced odds of burnout was observed among physicians who worked ⩽20 h/week (vs 31–40 h/week, adjusted odds ratio (aOR) 0.03, 95% confidence interval (CI) 0.002–0.56) and who had a greater perceived level of clinical support (aOR 0.70, 95% CI 0.62–0.80). Physicians with higher levels of depressive symptoms had higher odds of burnout (aOR 18.32, 95% CI 6.75–49.73). Resilience, mean (SD) CD-RISC score, was lower in physicians who met burnout criteria compared to those who did not (62.6 (11.1) vs 70.0 (11.3); p  < 0.001). Conclusions: Over one-third of palliative medicine physicians meet burnout criteria. The provision of enhanced organisational and colleague support is paramount in both the current and future pandemics.